The parent trap [videorecording (DVD)] / [presented by] Walt Disney ; written for the screen and directed by David Swift ; The parent trap II / [presented by] The Disney Channel ; produced by Joan Barnett ; written by Stuart Krieger ; directed by Ronald F. Maxwell. - Swift, David, 1919-2001; Mills, Hayley; O'Hara, Maureen, 1920-2015; Keith, Brian, 1921-1997; Kästner, Erich, 1899-1974 (Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2005)
"Parent trap": Susan and Sharon are identical twins that are separated by birth. Once they realize who they are, they make a plan to switch place with the high hopes of getting their parents back together again. "Parent trap II": Now grown up, Sharon is a single mom whose daughter meets Mary and the girls turn into scheming matchmakers.